Strategic design of long-term climate policy instrumentations, with exemplary EU focus. (1st June 2017) - Huppes, Gjalt; Deetman, Sebastiaan; Huele, Ruben; Kleijn, René; De Koning, Arjan; van der Voet, Ester
Abstract : The Paris climate goal requires unprecedented emission reduction, while CO2 concentrations are now rising faster than ever. Internally inconsistent instrumentation has developed on the go, not fit for deep reduction. Mainly national technology-specific instruments, for example, have made the EU pure cap-and-trade system superfluous and have fragmented electricity markets. Systematic instrumentation design requires an adequate categorization of instruments, newly developed here for that purpose. This instrument ordering links to generality and bindingness. Starting points for any instrumentation design are sparseness, completeness, and non-overlap. Details in instrumentations may further depend on specific circumstances in different countries and regions. Planning & Control starts with technology-specific instrumentation, with subsidies and standards to reduce fossil emissions in electricity production; effective Fleet Standards for transport; dynamic standards and permits regarding industry emissions; and standards and technology subsidies squeezing out fossils use in buildings and appliances. Subsidies create learning curves. Consistency and effectiveness tend to require centralization. Institutionalism uses two core institutional instruments. A comprehensive upstream emission tax with proceeds to the country or state level creates incentives. An open-to-all, real-time priced electricity market enables also small-scale renewables and secondary producers on the grid. Infrastructure is provided publicly. A level playing field results for mostly decentral climate action, both public and private. Policy relevance Technical instrument choices may seem neutral but cannot be so: policy is about choices. Two governance strategies are now mutually competing and counteracting. Planning & Control links to welfare theory and optimization, with broad integration of several policy goals, measurable targets, and deep public–private cooperation. Institutionalism has a background in history, economics, sociology, and political science, with institutions driving long-term development. Incentives and option creation are central, indicating results only roughly. There is strict public–private delimitation. These different views on governance lead to mutually exclusive sets of instruments. Explicit instrumentation strategies are required for consistency, effectiveness, and legitimacy. Internationally, Planning & Control requires binding country caps for (almost) all countries, UN-type. Institutionalism requires a limited agreement on a high rising emission tax, open for all countries to join a starting group, WTO-type. Choices are ultimately based on governance preferences.